Main Trends and Challenges of Digitalisation in Higher Education - Bazeliuk, Oleksandr (Pedagogical Discourse, 2021)
The article enlightens the main trends and challenges of digitalization in higher education institutions. The author emphasises that such a transition has become a significant challenge for the higher education system in Ukraine and the world. The analysis of regulative and scientific sources allowed to single out a number of trends, in particular: there will be a transition to a digital university as a set of digital educational services and educational content soon; strengthening competition between universities, coming out the possibility of organizing remote interaction as a primary feature of digital technologies; universities’ reach of new target groups with limited access to higher education due to living conditions, geographical location, etc.; digital learning resources can promote international mobility of higher education student and staff; cooperation becomes an essential part of university education; digital technologies contribute to the search for new virtual locations and forms such as digital campuses, virtual exhibition hubs, coworking centres, etc.; digital innovations are not only technical but also structural changes which are equally important to ensure this process. The general trend of using adaptive educational systems and data-based systems, which will make the educational process in higher education institutions more transparent and measurable, is outlined. The author points out that digital technologies have limitations in scalability, and the development of such systems requires significant funding due to the high level of knowledge and the need for constant updating. It is revealed that the imperfection of the regulatory framework is becoming a deterrent to the introduction of digital innovations. For example, the outdated copyright does not allow to fully realize the potential of digital technologies in terms of ensuring open access to quality education or academic integrity. The author considers perspective the study of new virtual forms of interaction between the educational process participants and using the distributed computing and artificial intelligence technologies to create adaptive educational systems.